Attitudes to smoking cessation and triggers to relapse among Chinese male smokers - Fisher K John; Yang Tingzhong; Li Fuzhong; Danaher Brian G (BMC, 2006)
Abstract Background Smoking is related to many diseases, and the relapse to smoking after cessation in China is noticeable. We examined the attitudes of Chinese male smokers regarding smoking cessation and reasons for relapse. Methods We interviewed 201 male smokers in Hangzhou City, Zhejiang province, China who had tried to quit smoking at least once in order to identify reasons for quitting and situations triggering relapse. Results The most significant reported reasons for quitting included personal health (77.1%), the cost of cigarettes (53.7%), and family pressures to quit (29.9%). The most common factors triggering relapse were social situations (34.3%), feeling negative or down (13.4%) and times of being alone (8.4%). Conclusion Health and family concerns, personal factors, the influence of others and a lack of cessation resources were cited as salient factors concerning smoking cessation among male smokers in this study. Effective smoking control efforts in China will require attention to these influences if China is to curb its current smoking epidemic.